SYNTACTIC DEVICES USED IN POETIC LANGUAGE - Karimova Shaxnoza Karimovna; Gulbagira Saurikova (Modern American Journals, 2025)
This article explores the syntactic and stylistic features of modern English poetry, with occasional references to similarities in modern Uzbek poetry. Beginning with an overview of the transition from Victorian poetic traditions to modernist innovations in the early 20th century, the paper highlights the contributions of literary critic David Perkins and examines the works of prominent poets such as T.S. Eliot, W.B. Yeats, Ezra Pound, and Kenneth Koch. It analyzes how syntactic devices—such as sentence fragmentation, inversion, and repetition—play a critical role in shaping poetic meaning and emotional resonance. Special attention is given to forms of syntactic repetition, especially anaphora, as well as other rhetorical devices like ellipsis, silence, and rhetorical questions. The study concludes that these syntactic-stylistic elements contribute significantly to the expressiveness and aesthetic quality of modern poetry in both English and Uzbek traditions.
Keywords: Modern English poetry, syntax, stylistics, anaphora, epiphora, repetition, modernism, poetic devices, rhetorical figures, Uzbek poetry, free verse, sentence structure, poetic syntax, emotional expressiveness.